The Impact of Social Media Advertising on Stimulating Purchasing Intent from the Audience’s Perspective (Facebook and YouTube as a Case Study) - Yaser, Marwan Khashlan (Journal of Ecohumanism, 2025)
The researcher seeks in his study entitled (Advertising via social networking sites and their role in stimulating purchasing desire from the public’s point of view (Facebook - YouTube as a model)) to determine the most important objectives to measure the extent to which social networking sites contribute to stimulating purchasing desire from the public’s point of view and to identify the most important sites that the public follows via social networking sites to reach the goals that the research seeks to achieve by using the researcher’s survey method and a random sample of the public exposed to those sites. To know the role of digital platforms, which are an integral part of citizens’ daily lives, and a powerful tool for advertising and extrapolating information, especially in the field of promoting goods and services Because they have effective means to reach a wide and rapid audience, as they provide diverse opportunities for shopping through those social sites more effectively than traditional media, and this allows followers to interact with advertising content through comments, posts and reviews, which increases their connection to sales and promotion topics. In this context, these pages interact with their audience through various advertisements and different methods. In addition, platforms such as Facebook, Twitter, and Instagram allow viewers to share their opinions about the quality of the advertised materials and exchange views with others, which enhances their role in shaping a mental image. In this regard, the research reached a range of results, the most important of which are: The research proved the contribution of electronic advertisements via social networking sites to attracting users towards the goods and products displayed via Facebook and YouTube, which fulfills their purchasing desire. Most users of social networking sites also keep up with everything new in the advertisements displayed via these sites.